INFLUENCE OF PRINCIPALS' DIGITAL COMMUNICATION LITERACY ON ICT INTEGRATION MANAGEMENT OUTCOMES IN PUBLIC SECONDARY SCHOOLS IN KITUI CENTRAL SUB COUNTY, KENYA - Philip, Janet; Thinguri, Ruth (African Journal of Education and Practice, 2022)
Purpose: Integration of ICT in educational management is becoming an effective factor in running schools in Kenya and yet there are many public secondary schools which are still stuck in the inefficient analogue methods in Kitui Central. The aim of this investigation was to look at the influence of principals' digital communication literacy on ICT integration management outcomes in public secondary schools in Kitui Central Sub County, Kenya. Methodology: The study was guided by Connectivism and Diffusion of Innovations theories. The study embraced the concurrent triangulation design. The target population was 301 participants which comprised of 50 principals, 200 Heads of departments, 50 BoM chairpersons and 1 ICT Sub County Director. The sample was 172 participants comprising of 28 principals, 115 HoDs, 28 BoM chairpersons and 1 ICT director. The principals were sampled using purposive sampling as well as the BoM chairpersons. The HoDs were randomly sampled. There was questionnaire for HoDs and and interview schedule for principals. Quantitative data was analyzed in descriptive statistics and presented in tables, frequencies and percentages. Qualitative data was analyzed thematically and presented in verbatim citations as well narratives. Findings: From the findings, it was accepted that most principals were familiar with computer operations. However, there were issues when it came to typesetting, Skype, organizing, copying, pasting and navigation of files using windows. Consequently, there was need to beef up digital communication among the principals. Unique Contribution to Theory, Policy and Practice: The Connectivism and Diffusion of Innovations theories were used. The first one is about making decisions on the fast-changing realities while the second is on generalizing inventions in communities and accepting or rejecting them. The theories helped making decisions and accepting new changes. The study established that principals still lacked digital communication literacy, calling for more training in ICT. The theories were validated in that there was need to make decisions on new technology and more importantly, accept these changes like ICT. It was recommended that the government should put in place modalities of improving digital communication literacy.